Effect of Realistic Mathematical Approaches against Results Learning Mathematics and Student Learning Motivation SDN 102119 Nagaraja Serdang Bedagai - Maria Melfa Simanjuntak; Hasratuddin; Zulkifli Matondang (Britain International for Academic Research (BIAR) Publisher, 2020)
Mathematics learning outcomes obtained by students at least describe the achievement of learning objectives to be achieved. But the learning outcomes of students at SD Negeri 102119 Nagaraja are still relatively low with a low level of student motivation so that it influences the teaching and learning process. With one alternative that can help using the Realistic Mathematical Approach (PMR) can improve student learning outcomes and motivation to learn mathematics. Therefore, this study aims to examine the Effect of Realistic Mathematical Approaches on Learning Outcomes of Mathematics; Effect of Realistic Mathematical Approaches on Student Learning Motivation; and Great influence of learning approaches on student learning outcomes in mathematics and student motivation. This research is a quasi-experimental research. The population in this study were all fourth grade students of SD Negeri 102119 Nagaraja Serdang Bedagai, totaling 54 students. The instrument used consisted of a test of learning outcomes and a motivation questionnaire. Data were analyzed with the Simple Regression Analysis Test. Based on the results of the analysis the results of the study are obtained that the Realistic Mathematics Approach gives an effect on the mathematics learning outcomes of fourth grade students of SD Negeri 102119 Nagaraja Serdang Bedagai because the value of Sig. equal to 0,00 <0,05 with t count 7,158> t table 2,064; The Realistic Mathematics Approach does not have an effect on student motivation because the value of Sig. of 0.84> 0.05 with t count 0.193 <t table 2.064; and The magnitude of the effect of the learning approach on mathematics learning outcomes 68.1% and the effect of the learning approach on learning motivation 0.2% while the remaining 31.7% is influenced by factors other than the learning approach.